A kind of high hardness foamed silicone rubber and preparation method

By using modified aluminum hydroxide and a variety of mechanical reinforcement agents in foamed silicone rubber, its hardness and compressive strength are improved, and the shear thickening gel in carbon nanotubes is used to enhance the compressive deformation resistance, solving the stability and shaking problems during filling of new energy batteries.

CN119570264BActive Publication Date: 2025-04-29ZHEJIANG LEXUS NEW ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510111408.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-04-29
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

When used for filling new energy batteries, existing foamed silicone rubber is insufficient in flexibility, resulting in the inability to effectively stabilize the battery modules, and battery shaking is prone to occur under external interference.

Method used

By using vinyl triethoxysilane for surface treatment as a flame retardant, and combining a mixture of gas-phase white carbon black, vinyl MQ silicone resin and modified carbon nanotubes with surface treatment as a mechanical reinforcement agent, the hardness and compressive strength of foamed silicone rubber are enhanced, while using the shear thickening gel in carbon nanotubes to enhance the compressive deformation resistance.

Benefits of technology

The foamed silicone rubber has high hardness and excellent compressive strength while maintaining low density and good rebound, effectively solving the problems of battery module stability and shaking resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570264B_ABST
    Figure CN119570264B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of foamed silicone rubber and production and preparation process, and particularly to a high-hardness foamed silicone rubber and a preparation method thereof, comprising 1-20 parts of hydrogen-containing polysiloxane, 10-70 parts of hydroxyl-terminated polymethylvinylsiloxane, 1-30 parts of a mechanical reinforcing agent, 10-80 parts of a flame retardant, and 0.05-0.3 parts of a catalyst, wherein the mechanical reinforcing agent is a mixture of fumed silica, vinyl MQ silicone resin, and surface-treated carbon nanotubes, so that the foamed silicone rubber has high hardness and its density does not increase, and at the same time, the shear thickening gel filled and adsorbed in the carbon nanotubes is used, so that when the foamed silicone rubber material is compressed, it can quickly harden so that the originally soft carbon nanotubes form a skeleton support for the foamed silicone rubber, thereby improving the compressive strength and permanent deformation of the foamed silicone rubber, and thereby forming a foamed silicone rubber material that can be applied to new energy battery support and has good hardness, low density, excellent compressive strength and resilience.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foamed silicone rubber and production and preparation technology, and in particular to high-hardness foamed silicone rubber and a preparation method thereof. Background Art

[0002] Foamed silicone rubber is a special type of silicone rubber that produces gas through a physical or chemical foaming process, forming a closed-cell or open-cell foam structure in the cured rubber. This structure gives foamed silicone rubber the characteristics of being light, soft, flexible, and having good thermal insulation and sound insulation properties.

[0003] This material is commonly used in a variety of applications, especially where heat resistance, oxidation resistance, weather resistance, water resistance and compression set recovery are required. It is widely used in the automotive, electronics, medical, construction, aerospace and other industries, including seals, shock pads, thermal insulation materials, muffler elements and various vibration reduction and filling parts.

[0004] The foamed silicone rubber of the present invention is used in new energy batteries in new energy vehicles. The current foamed silicone rubber is mostly used in thermal management, buffering and shockproofing, sealing and waterproofing, filling insulation and heat insulation and flame retardancy of new energy batteries due to its soft characteristics. When the foamed silicone rubber is used for filling, although it can effectively reduce the shock of the new energy battery, it is too soft, resulting in the inability to stably position the battery assembly. Once the new energy battery is disturbed by external force, the foamed silicone rubber is greatly compressed. Once the foamed silicone rubber is compressed, the filling space becomes larger, and the battery will shake.

[0005] Therefore, this application needs to develop a foamed silicone rubber with high hardness, which can change the soft characteristics of the foamed silicone rubber and reduce the compression deformation of the foamed silicone rubber while having shock-absorbing properties.

[0006] In the Chinese patent application number 202310327955.7, a foamed conductive silicone rubber and its preparation method are disclosed, including the following raw materials in parts by weight: 90-110 parts of methyl vinyl silicone rubber, 15-25 parts of modified conductive filler, 0-15 parts of reinforcing filler, 1-5 parts of dispersing aid, 2-5 parts of platinum vulcanization system, and 2-8 parts of foaming agent. The foamed conductive silicone rubber modifies the conductive filler on the surface, increases the compatibility of the conductive filler with the methyl vinyl silicone rubber, and makes the conductive silicone rubber have high conductivity; it also improves the vulcanization rate and foaming degree of the conductive silicone rubber base to a certain extent, so that the foamed conductive silicone rubber has the excellent properties of high hardness and uniform foaming; strictly control the addition amount and proportion of each raw material, so that the two processes of crosslinking and foaming of the foamed conductive silicone rubber are fully reacted, forming a dense crosslinking network, foaming uniformly, and preparing a foamed conductive silicone rubber with high hardness and low density.

[0007] Although, in the foamed conductive silicone rubber disclosed in the above patent document, the conductive filler is surface modified by high-content hydroxyl silicone oil, thereby increasing the interfacial adhesion between the conductive filler and the resin, the high-content hydroxyl silicone oil will affect its foaming efficiency. The hydroxyl silicone oil will react competitively with the foaming agent or catalyst, thereby affecting the generation and stability of bubbles; and the high-content hydroxyl silicone oil will lead to an excessive amount of silicone rubber glue, which will reduce the cross-linking density and cause incomplete cross-linking, which may affect the mechanical properties of the foamed silicone rubber and cause processing difficulties.

[0008] Therefore, when this type of foamed conductive silicone rubber is used as a supporting material for new energy batteries, although it can solve the technical problems of conductivity and hardness, its mechanical properties such as compressive strength, dimensional stability and compression permanent set are far from meeting the needs of use.

[0009] In addition, in a Chinese patent with patent application number 202210290328.6, a silicone rubber foam material and a preparation method thereof are disclosed. A shear thickening gel that is well compatible with silicone rubber is used to prepare a silicone rubber foam material with the advantages of high rebound and low compression deformation. At the same time, the excellent resilience of the expanded microspheres is used to eliminate the problem of easy adhesion of the foam wall after compression of the foam material caused by the shear thickening gel, so that the foamed silicone rubber can be better used in the fields of shock absorption and impact resistance.

[0010] However, when expanded microspheres are used in foamed silicone rubber, the production cost is high, and the dispersibility of the expanded microspheres will lead to limited foaming effects and uneven foaming. Furthermore, although the resilience of the expanded microspheres will eliminate the problem of cell wall adhesion when the foamed silicone material is compressed, the cell wall adhesion cannot be restored in some areas. In addition, when the foamed silicone rubber prepared using expanded microspheres is used in a high temperature environment, it will lead to problems such as reduced strength, reduced hardness, and poor aging resistance.

[0011] Therefore, although this type of silicone rubber foam material has good resilience and compressive strength when used as a supporting material for new energy batteries, there is still a certain gap in permanent deformation performance, anti-aging performance at high temperature (new energy batteries will continue to generate heat when working), and flame retardant performance. Summary of the invention

[0012] In view of the above problems, the present invention provides a high-hardness foamed silicone rubber and a preparation method thereof. The flame retardant property of the foamed silicone rubber is improved by using aluminum hydroxide surface-treated with vinyl triethoxysilane as a flame retardant. At the same time, a mixture containing fumed silica surface-treated with methyl vinyl silazane, vinyl MQ silicone resin and surface-treated carbon nanotubes is used as a mechanical reinforcing agent (i.e., filler), so that the foamed silicone rubber has high hardness and its density does not increase. At the same time, the shear thickening gel filled and adsorbed in the carbon nanotubes can quickly harden when the foamed silicone rubber material is compressed, so that the originally soft carbon nanotubes form a skeleton support for the foamed silicone rubber, thereby improving the compressive strength and permanent deformation performance of the foamed silicone rubber. At the same time, the surface of the carbon nanotubes is treated with vinyl trimethoxysilane to improve the interface compatibility between the carbon nanotubes and the silicone rubber, and then the adsorption of the carbon nanotubes to the thickening gel is used to eliminate the problem of compression and bonding of the bubble wall of the shear thickening gel, thereby forming a foamed silicone rubber material that can be used for supporting new energy batteries and has good hardness, low density, excellent compressive strength and resilience.

[0013] To achieve the above object, the present invention provides the following technical solutions:

[0014] A high-hardness foamed silicone rubber, comprising, by weight:

[0015] 1-20 parts of hydrogen-containing polysiloxane;

[0016] 10-70 parts of hydroxyl-terminated polymethylvinylsiloxane;

[0017] Mechanical reinforcing agent 1-30 parts;

[0018] Flame retardant 10-80 parts;

[0019] Catalyst 0.05-0.3 parts;

[0020] Wherein, the vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.1%-6%, the viscosity is 500-50000mPas, and the hydroxyl content is 0.4%;

[0021] The chemical formula of the hydroxyl-terminated polymethylvinylsiloxane is:

[0022] ;

[0023] In the formula, m and n are integers greater than zero.

[0024] The mechanical reinforcing agent comprises filler 1, filler 2 and filler 3 in a weight ratio of 3:6:1, wherein filler 1 is fumed silica surface-treated with methylvinylsilazane, and the specific surface area of ​​the fumed silica is 100-400m2 / g, the filler 2 is a vinyl MQ silicone resin, the viscosity of the vinyl MQ silicone resin is 2000-100000 mPas, the vinyl content is 1-8%, and the filler 3 is a modified carbon nanotube;

[0025] The chemical formula of the vinyl MQ resin is:

[0026] ;

[0027] wherein at least one of R, R' or R" is a vinyl group.

[0028] Preferably, the vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.2-2%, and the viscosity of the hydroxyl-terminated polymethylvinylsiloxane is 4000-6000 mPa.s; the specific surface area of ​​the fumed silica is 250-350 m 2 / g;

[0029] The flame retardant is aluminum hydroxide surface-treated with vinyltriethoxysilane, and the particle size of the aluminum hydroxide is 1 micron;

[0030] The catalyst is a Castell platinum catalyst, and the platinum concentration of the Castell platinum catalyst is 5000 ppm.

[0031] As an improvement, the carbon nanotubes are carbon nanotubes with both ends opened, and shear thickening gel is adsorbed inside the carbon nanotubes. The shear thickening gel is a lightweight shear thickening gel. The carbon nanotubes are seamless carbon nanotubes formed by curling a single layer or multiple layers of graphite sheets around a central axis at a certain spiral angle. Generally, both ends are closed. In this state, the carbon nanotubes have a small specific surface area, few adsorption sites for the shear enhancing gel, and low adsorption performance. It is necessary to open the two ends of the carbon nanotubes to enhance the adsorption performance of the carbon nanotubes for the shear enhancing gel.

[0032] In addition, the shear enhanced gel of the present application preferably adopts a lightweight shear thickening gel, such as that disclosed in the Chinese patent with patent application number 202210290328.6, wherein a polydimethylsiloxane solution is prepared by polydimethylsiloxane, boric acid and its derivatives and an organic solvent, and a condensation reaction is carried out, and then the unreacted boric acid and its derivatives and the organic solvent are removed to obtain a shear thickening gel; this type of shear thickening gel reduces the use of nano-silica and can be better adsorbed by carbon nanotubes.

[0033] As an improvement, the carbon nanotubes are modified carbon nanotubes having vinyl groups on the surface. Vinyl functional groups are formed on the surface of the carbon nanotubes, which can improve the compatibility of the carbon nanotubes with silicone rubber and improve the dispersibility of the carbon nanotubes.

[0034] As an improvement, the carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes, the diameter of the carbon nanotubes is 10-30nm, and the length of the carbon nanotubes is 1-3μm, preferably the diameter of the carbon nanotubes is 15nm and the length is 2μm, which reduces the difficulty of dispersing the carbon nanotubes in silicone rubber while maintaining the adsorption performance of the carbon nanotubes on the shear thickening gel.

[0035] In addition, the present invention also provides a method for preparing the high-hardness foamed silicone rubber described in any one of the above items, comprising the following steps:

[0036] Step a, by weight, adding 9-63 parts of hydroxyl-terminated polymethylvinylpolysiloxane, 10-80 parts of flame retardant, and 10-30 parts of mechanical reinforcing agent into a planetary mixer, stirring at room temperature for 1 hour to obtain a base material, and dividing the base material into two parts, namely component A and component B;

[0037] Step b, adding 1-20 parts of hydrogen-containing polysiloxane to component A and stirring evenly to obtain material A;

[0038] Step c, adding 1-7 parts of hydroxyl-terminated polymethylvinyl polysiloxane and 0.05-0.3 parts of Castaplatin catalyst to component B and stirring evenly to obtain material B;

[0039] Step d: Take one portion of material A and one portion of material B in a weight ratio of 1:1, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Put the foamed silicone rubber A into a 200°C oven and bake it for 1 hour to obtain foamed silicone rubber B. The obtained foamed silicone rubber B has a Shore A hardness of 30-60 and a density of 0.6-0.8 g / cm 3 , tensile strength is 0.8-1.5MPa, flame retardancy is V0, and compressive stress is 200-400kPa under 10% compressive strain.

[0040] As an improvement, the flame retardant preparation method in step a comprises the following steps:

[0041] Add 100 parts of aluminum hydroxide into a high-speed mixer, start stirring and add 1 part of vinyl triethoxysilane into the mixer by spraying, stir at room temperature for 10 minutes, then increase the temperature in the mixer to 90°C and stir for 2 hours, then increase the temperature to 150°C and continue stirring for 30 minutes to obtain a flame retardant.

[0042] As an improvement, the preparation method of the filler 1 contained in the mechanical reinforcement agent in step a comprises the following steps:

[0043] Add 5 parts of fumed silica to a high-speed mixer, start stirring and dropwise add 1 part of tetramethyldivinylsilazane to the mixer, stir at room temperature for 2 hours, then raise the temperature in the mixer to 90°C and stir for 2 hours, then raise the temperature to 150°C and continue stirring for 5 hours to obtain filler 1.

[0044] As an improvement, the preparation method of the filler three contained in the mechanical reinforcement agent in step a comprises the following steps:

[0045] Step a1, soaking 10 parts of carbon nanotubes in a mixed acid composed of sulfuric acid and nitric acid, the mixed acid is prepared by mixing and reacting at 105-115° C., wherein the mass ratio of sulfuric acid to nitric acid is 2-4:1, so that the surface of the carbon nanotubes is carboxylated, and at the same time, the openings at both ends of the carbon nanotubes are opened by using a strong acid;

[0046] Step a2, at 30-50° C., adding tetraethyl orthosilicate and vinyl triethoxysilane to a mixed solution of water and ethanol in which surface carboxylated carbon nanotubes are dissolved, and simultaneously adding part of ammonia water for reaction; then adding the remaining mixture and ammonia water respectively, wherein the feed mass ratio of the surface carboxylated carbon nanotubes, the mixture of tetraethyl orthosilicate and vinyl triethoxysilane, and ammonia water is 1:1.1:1.1, the feed mass ratio of water to ethanol is 1:1.05, and the feed mass ratio of one of tetraethyl orthosilicate and vinyl triethoxysilane to the other is controlled within 3 times, and after the reaction is completed, modified carbon nanotubes with open ends and vinyl groups on the surface are obtained;

[0047] Step a3: After the prepared modified carbon nanotubes are rinsed with clean water and dried, the carbon nanotubes are mixed with a shear thickening gel and immersed for 3 hours. The carbon nanotubes are sieved out from the shear thickening gel and dried to obtain filler three.

[0048] The beneficial effects of the present invention are:

[0049] (1) The present invention adds modified carbon nanotubes to the existing mechanical reinforcing agent of foamed silicone rubber, and utilizes the modified carbon nanotubes to enhance the compressive deformation resistance of the foamed silicone rubber, so that the foamed silicone rubber has low density, softness and compressibility. At the same time, the excellent damping performance and reversible soft-hard conversion performance of the shear thickening gel are utilized to enable the carbon nanotubes to switch between softness and hardness. When the foamed silicone rubber is compressed, the foamed silicone rubber can have a strong ability to resist compression deformation. When used in new energy battery support, it can absorb shock and energy without excessive permanent deformation and compression, thereby reducing the size change. At the same time, the carbon nanotubes avoid the problem of foam silicone rubber bubble wall adhesion caused by the shear thickening gel.

[0050] (2) The present invention modifies the surface of carbon nanotubes so that the carbon nanotubes, which originally have poor compatibility with silicone rubber, can be well cross-linked with silicone rubber through vinyl functional groups, thereby avoiding the poor dispersion of carbon nanotubes and effectively improving the hardness, tensile strength, tear strength, electrical conductivity and thermal conductivity of foamed silicone rubber;

[0051] (3) The present invention utilizes the hydroxyl group (-OH) in hydroxyl-terminated polymethylvinylsiloxane and the silicon-hydrogen (-Si-H) bond in hydrogen-containing polysiloxane to generate silanol (-Si-OH) and hydrogen under the action of a catalyst, and utilizes hydrogen for foaming. At the same time, hydroxyl-terminated polymethylvinylsiloxane generally contains vinyl functional groups (-CH=CH2). These vinyl groups can react with the silicon-hydrogen bonds in hydrogen-containing polysiloxane under the activation of a catalyst to form a cross-linked structure, thereby ensuring the hardness of the silicone rubber while ensuring the foaming. Moreover, this cross-linking reaction enables the silicone rubber material to have better mechanical properties and thermal stability after curing.

[0052] (4) The present invention adds a vinyl MQ resin with an ethylene content of 1%-8% as a mechanical reinforcing agent of the system to further increase the crosslinking density. When the ethylene content of the MQ resin reaches 1%-8%, the vinyl MQ resin can play an important role as a mechanical reinforcing agent of the system. As the vinyl content increases, the resin is more likely to undergo vinyl addition crosslinking with compounds containing active hydrogen. This crosslinking reaction not only increases the crosslinking density of the material, but also significantly enhances its mechanical properties, such as improving tensile strength, tear strength, and hardness, while maintaining good elasticity;

[0053] (5) The present invention uses vinyl triethoxysilane to treat the flame retardant surface. The ethoxy groups are hydrolyzed in the presence of water to form silanol groups. These silanol groups can form chemical bonds with hydroxyl groups or other active sites on the surface of the flame retardant. At the same time, the exposed vinyl groups and the polymer matrix have better chemical compatibility. On the basis of not destroying the stability of the foaming reaction, the flame retardant properties of the silicone rubber are ensured while further improving the hardness of the foamed silicone rubber.

[0054] (6) The present invention uses hydrogen-containing polysiloxane to treat the catalyst surface, so that the hydrogen-containing polysiloxane is mixed with the catalyst. These catalysts can promote the addition reaction between the silicon-hydrogen bond (-Si-H) of the hydrogen-containing polysiloxane and the hydroxyl group (-OH) or unsaturated double bond on the surface of the filler. In addition, in the dehydrogenation condensation reaction, a silyl ether bond (-Si-O-Si-) connecting the filler and the polymer matrix is ​​formed, which further improves the cross-linking strength, ensures the strength of the silicone rubber, and improves the surface hardness of the molded silicone rubber.

[0055] In summary, the present invention has the advantages of excellent flame retardancy, stable mechanical properties, high strength, high hardness, small compression deformation, etc., and is particularly suitable for the technical field of foamed silicone rubber preparation for new energy fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 is a SEM image of the modified carbon nanotubes of the present invention;

[0057] Figure 2 This is a SEM image of the foamed silicone rubber of Preparation Example 1 of the present invention;

[0058] Figure 3 This is a SEM image of the foamed silicone rubber of Preparation Example 2 of the present invention;

[0059] Figure 4 This is a SEM image of the foamed silicone rubber of Preparation Example 3 of the present invention;

[0060] Figure 5 This is a SEM image of the foamed silicone rubber of Preparation Example 4 of the present invention;

[0061] Figure 6 This is a SEM image of the foamed silicone rubber of Preparation Example 5 of the present invention;

[0062] Figure 7 This is a SEM image of the foamed silicone rubber of Preparation Example 6 of the present invention;

[0063] Figure 8 This is the SEM image of the foamed silicone rubber prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0064] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0065] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0066] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0067] Example:

[0068] A high-hardness foamed silicone rubber, comprising, by weight:

[0069] 1-20 parts of hydrogen-containing polysiloxane;

[0070] 10-70 parts of hydroxyl-terminated polymethylvinylsiloxane;

[0071] Mechanical reinforcing agent 1-30 parts;

[0072] Flame retardant 10-80 parts;

[0073] Catalyst 0.05-0.3 parts;

[0074] Wherein, the vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.1%-6%, the viscosity is 500-50000mPas, and the hydroxyl content is 0.4%;

[0075] The mechanical reinforcing agent comprises filler 1, filler 2 and filler 3 in a weight ratio of 3:6:1, wherein filler 1 is fumed silica surface-treated with methylvinylsilazane, and the specific surface area of ​​the fumed silica is 100-400m 2 / g, the filler 2 is a vinyl MQ silicone resin, the viscosity of the vinyl MQ silicone resin is 2000-100000mPas, and the vinyl content is 1-8%. Preferably, the vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.2-2%, and the viscosity of the hydroxyl-terminated polymethylvinylsiloxane is 4000-6000mPa.s; the specific surface area of ​​the fumed silica is 250-350m 2 / g, the filler three is a modified carbon nanotube; wherein the carbon nanotube is a carbon nanotube with both ends opened, and shear thickening gel is adsorbed inside the carbon nanotube. The carbon nanotube with both ends opened can greatly improve the adsorption capacity of the shear thickening gel, and the shear thickening gel is a lightweight shear thickening gel. Since the shear thickening gel itself is a non-Newtonian fluid, its own viscosity increases with the increase of shear rate. Therefore, the shear thickening gel needs to be kept in a fluid state so that the carbon nanotubes and the shear thickening gel are mixed and impregnated, so that the carbon nanotubes can adsorb the shear thickening gel, and the shear thickening gel uses a lightweight shear thickening gel that does not contain nano-silica particles, such as the shear thickening gel component recorded in the Chinese patent with patent application number 202210290328.6 in the background technology.

[0076] In addition, the carbon nanotubes are modified carbon nanotubes having vinyl groups on the surface. Vinyl functional groups are formed on the surface of the carbon nanotubes, and the problem of dispersibility of the carbon nanotubes in silicone rubber is solved by using the vinyl functional groups.

[0077] The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes. The diameter of the carbon nanotubes is 10-30 nm, and the length of the carbon nanotubes is 1-3 μm. When the diameter of the carbon nanotubes meets the requirements of shear thickening gel adsorption, the length of the carbon nanotubes needs to be as short and moderate as possible to avoid excessive length of the carbon nanotubes, which may result in the inability to disperse the carbon nanotubes and uneven distribution.

[0078] The flame retardant is aluminum hydroxide surface-treated with vinyl triethoxysilane. The particle size of the aluminum hydroxide is 1 micron. When encountering a flame, the aluminum hydroxide will release water. This process absorbs a large amount of heat, which helps to reduce the temperature of the material surface and delay the spread of the flame. At the same time, the released water vapor can also dilute the combustible gas near the flame, further slowing the spread of the flame. In addition, the aluminum hydroxide can decompose to generate aluminum oxide (Al2O3) and water (H2O). This decomposition process not only absorbs a large amount of heat, but also increases the thermal stability of the material. The layer formed by the generated aluminum oxide can also serve as a physical barrier to further protect the silicone rubber from thermal decomposition.

[0079] The catalyst is a Castell platinum catalyst having a platinum concentration of 5000 ppm and is used for catalyzing the addition reaction between silane and a compound containing a silicon-hydrogen bond.

[0080] A method for preparing the high-hardness foamed silicone rubber described in any one of the above, comprising the following steps:

[0081] Step a, by weight, adding 9-63 parts of hydroxyl-terminated polymethylvinylpolysiloxane, 10-80 parts of flame retardant, and 10-30 parts of mechanical reinforcing agent into a planetary mixer, stirring at room temperature for 1 hour to obtain a base material, and dividing the base material into two parts, namely component A and component B;

[0082] Step b, adding 1-20 parts of hydrogen-containing polysiloxane to component A and stirring evenly to obtain material A;

[0083] Step c, adding 1-7 parts of hydroxyl-terminated polymethylvinyl polysiloxane and 0.05-0.3 parts of Castaplatin catalyst to component B and stirring evenly to obtain material B;

[0084] Step d: Take one portion of material A and one portion of material B in a weight ratio of 1:1, mix them quickly and evenly, and obtain foamed silicone rubber A after reacting for 10 minutes. Put the foamed silicone rubber A into a 200° C. oven and bake it for 1 hour to obtain foamed silicone rubber B.

[0085] Wherein, the preparation method of the flame retardant in step a comprises the following steps:

[0086] Add 100 parts of aluminum hydroxide into a high-speed mixer, start stirring and add 1 part of vinyl triethoxysilane into the mixer by spraying, stir at room temperature for 10 minutes, then increase the temperature in the mixer to 90°C and stir for 2 hours, then increase the temperature to 150°C and continue stirring for 30 minutes to obtain a flame retardant.

[0087] In addition, the preparation method of the filler 1 contained in the mechanical reinforcing agent in step a comprises the following steps:

[0088] Add 5 parts of fumed silica to a high-speed mixer, start stirring and dropwise add 1 part of tetramethyldivinylsilazane to the mixer, stir at room temperature for 2 hours, then raise the temperature in the mixer to 90°C and stir for 2 hours, then raise the temperature to 150°C and continue stirring for 5 hours to obtain filler 1.

[0089] Furthermore, the preparation method of the filler three contained in the mechanical reinforcing agent in step a comprises the following steps:

[0090] Step a1, soaking 10 parts of carbon nanotubes in a mixed acid composed of sulfuric acid and nitric acid, the mixed acid is prepared by mixing and reacting at 105-115° C., wherein the mass ratio of sulfuric acid to nitric acid is 2-4:1, so that the surface of the carbon nanotubes is carboxylated, and at the same time, the openings at both ends of the carbon nanotubes are opened by using a strong acid;

[0091] Step a2, at 30-50° C., adding tetraethyl orthosilicate and vinyl triethoxysilane to a mixed solution of water and ethanol in which surface carboxylated carbon nanotubes are dissolved, and simultaneously adding part of ammonia water for reaction; then adding the remaining mixture and ammonia water respectively, wherein the mass ratio of the surface carboxylated carbon nanotubes, the mixture of tetraethyl orthosilicate and vinyl triethoxysilane, and ammonia water is 1:1.1:1.1, the mass ratio of water to ethanol is 1:1.05, and the mass ratio of one of tetraethyl orthosilicate and vinyl triethoxysilane to the other is controlled within 3 times, and after the reaction is completed, modified carbon nanotubes with open ends and vinyl groups on the surface are obtained, such as Figure 1 As shown;

[0092] Step a3: After the prepared modified carbon nanotubes are rinsed with clean water and dried, the carbon nanotubes are mixed with a shear thickening gel and immersed for 3 hours. The carbon nanotubes are sieved out from the shear thickening gel and dried to obtain filler three.

[0093] In the step d, the obtained foamed silicone rubber B has a Shore A hardness of 30-60 and a density of 0.6-0.8 g / cm 3 , tensile strength is 0.8-1.5MPa, flame retardancy is V0, and compressive stress is 200-400kPa under 10% compressive strain.

[0094] Preparation Example 1:

[0095] 1000 g (equivalent to 50 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 5000 mPas, vinyl content 1.2%, hydroxyl content 0.4%), 600 g (30 parts) of flame retardant, 100 g (5 parts) of filler (fumed silica, specific surface area 300 m 2 / g), 200g (10 parts) of filler 2 (vinyl MQ silicone resin, viscosity 10000mPas, vinyl content 2%), and 34g (1.7 parts) of filler 3 (modified carbon nanotubes) were added to a planetary mixer and stirred at room temperature for 1 hour to obtain a base material, and then the base material was evenly divided into two parts, namely component A and component B. 100g (5 parts) of hydrogen-containing polysiloxane (viscosity 100 mPas, active hydrogen content 0.8%) was added to component A and stirred evenly, and 100g (5 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 5000mPas, vinyl content 1.2%, hydroxyl content 0.4%) and 1.2g (0.06 parts) of Castor platinum catalyst (platinum concentration of 5000ppm) were added to component B and stirred evenly.

[0096] When using, take 100 grams of component A and 100 grams of component B, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Then put the foamed silicone rubber 4 into a 200°C oven and bake it for 1 hour to finally obtain foamed silicone rubber B.

[0097] Preparation Example 2:

[0098] 1000 g (equivalent to 50 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 4000 mPas, vinyl content 0.2%, hydroxyl content 0.4%), 800 g (40 parts) of flame retardant, 100 g (5 parts) of filler (fumed silica, specific surface area 250 m 2 / g), 200g (10 parts) of filler 2 (vinyl MQ silicone resin, viscosity 2000mPas, vinyl content 1%), and 34g (1.7 parts) of filler 3 (modified carbon nanotubes) were added to a planetary mixer and stirred at room temperature for 1 hour to obtain a base material, which was then divided into two parts, namely component A and component B. 100g (5 parts) of hydrogen-containing polysiloxane (viscosity 100 mPas, active hydrogen content 0.8%) was added to component A and stirred evenly, and 100g (5 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 4000mPas, vinyl content 0.2%, hydroxyl content 0.4%) and 1.2g (0.06 parts) of Castor platinum catalyst (platinum concentration of 5000ppm) were added to component B and stirred evenly.

[0099] When using, take 100 grams of component A and 100 grams of component B, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Then put the foamed silicone rubber 4 into a 200°C oven and bake it for 1 hour to finally obtain foamed silicone rubber B.

[0100] Preparation Example 3:

[0101] 1000 g (equivalent to 50 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 50000 mPas, vinyl content 2%, hydroxyl content 0.4%), 600 g (30 parts) of flame retardant, 100 g (5 parts) of filler (fumed silica, specific surface area 350 m 2 / g), 100g (5 parts) of filler 2 (vinyl MQ silicone resin, viscosity 100000mPas, vinyl content 8%), and 34g (1.7 parts) of filler 3 (modified carbon nanotubes) were added to a planetary mixer and stirred at room temperature for 1 hour to obtain a base material, which was then divided into two parts, namely component A and component B. 100g (5 parts) of hydrogen-containing polysiloxane (viscosity 100 mPas, active hydrogen content 0.8%) was added to component A and stirred evenly, and 100g (5 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 50000mPas, vinyl content 2%, hydroxyl content 0.4%) and 1.2g (0.06 parts) of Castor platinum catalyst (platinum concentration of 5000ppm) were added to component B and stirred evenly.

[0102] When using, take 100 grams of component A and 100 grams of component B, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Then put the foamed silicone rubber 4 into a 200°C oven and bake it for 1 hour to finally obtain foamed silicone rubber B.

[0103] Preparation Example 4:

[0104] 900 g (equivalent to 9 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 500 mPas, vinyl content 0.1%, hydroxyl content 0.4%), 1000 g (10 parts) of flame retardant, 30 g (0.3 parts) of filler (fumed silica, specific surface area 100 m 2 / g), 60g (0.6 part) of filler 2 (vinyl MQ silicone resin, viscosity 2000mPas, vinyl content 1%), and 10g (0.1 part) of filler 3 (modified carbon nanotubes) were added to a planetary mixer and stirred at room temperature for 1 hour to obtain a base material, which was then divided into two parts, namely component A and component B. 100g (1 part) of hydrogen-containing polysiloxane (viscosity 100 mPas, active hydrogen content 0.8%) was added to component A and stirred evenly, and 100g (1 part) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 500mPas, vinyl content 0.1%, hydroxyl content 0.4%) and 5g (0.05 part) of Castor platinum catalyst (platinum concentration of 5000ppm) were added to component B and stirred evenly.

[0105] When using, take 100 grams of component A and 100 grams of component B, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Then put the foamed silicone rubber 4 into a 200°C oven and bake it for 1 hour to finally obtain foamed silicone rubber B.

[0106] Preparation Example 5:

[0107] 630 g (equivalent to 63 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 50000 mPas, vinyl content 6%, hydroxyl content 0.4%), 800 g (80 parts) of flame retardant, 128.5 g (12.8 parts) of filler 1 (fumed silica, specific surface area 400 m 2 / g), 128.5g (12.8 parts) of filler 2 (vinyl MQ silicone resin, viscosity 10000mPas, vinyl content 2%), and 43g (4.3 parts) of filler 3 (modified carbon nanotubes) were added to a planetary mixer and stirred at room temperature for 1 hour to obtain a base material, which was then divided into two parts, namely component A and component B. 200g (20 parts) of hydrogen-containing polysiloxane (viscosity 100 mPas, active hydrogen content 0.8%) was added to component A and stirred evenly, and 70g (7 parts) of hydroxyl-terminated polymethylvinyl polysiloxane (viscosity 50000mPas, vinyl content 6%, hydroxyl content 0.4%) and 3g (0.3 parts) of Castor platinum catalyst (platinum concentration of 5000ppm) were added to component B and stirred evenly.

[0108] When using, take 100 grams of component A and 100 grams of component B, mix them quickly and evenly, and react for 10 minutes to obtain foamed silicone rubber A. Then put the foamed silicone rubber 4 into a 200°C oven and bake it for 1 hour to finally obtain foamed silicone rubber B.

[0109] Preparation Example 6:

[0110] Same as Preparation Example 4, except that filler one is 42.8 g, filler two is 42.8 g, and filler three is 14.4 g.

[0111] Preparation Example 7:

[0112] Same as Preparation Example 5, except that filler one is 90 g, filler two is 180 g, and filler three is 30 g.

[0113] Comparative Preparation Example 1:

[0114] The same as Preparation Example 1, except that the mechanical reinforcing agent only contains filler 1.

[0115] Comparative Preparation Example 2:

[0116] The same as Preparation Example 1, except that the mechanical reinforcing agent only contains filler 1 and filler 2.

[0117] Comparative Preparation Example 3:

[0118] The same as Preparation Example 4, except that the content of filler 3 in the mechanical reinforcing agent is 8 g.

[0119] Comparative Preparation Example 4:

[0120] The same as Preparation Example 5, except that the content of filler 3 in the mechanical reinforcing agent is 80 g.

[0121] Comparative Preparation Example 5:

[0122] The same as Preparation Example 1, except that the carbon nanotubes of filler 3 in the mechanical reinforcing agent are not filled with the shear thickening gel for modification.

[0123] Comparative Preparation Example 6:

[0124] The same as Preparation Example 1, except that the carbon nanotubes of filler 3 in the mechanical reinforcing agent are not subjected to surface modification treatment and do not contain vinyl functional groups on the surface.

[0125] The performance tests of the foamed silicone rubber materials obtained in Preparation Examples 1-7 and Comparative Preparation Examples 1-6 were performed, and the density test was performed according to "GB / T533-2008 Determination of Density of Vulcanized Rubber or Thermoplastic Rubber", the Shore A hardness test was performed according to "GB / T531.1-2008 Shore A Hardness Test Method for Vulcanized Rubber or Thermoplastic Rubber Indentation", the tensile strength test was performed according to "GB / T 528-2009 Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber", the compression stress test under 10% compression strain was performed according to "SIS SS-ISO 7743-1992 Determination of Compression Stress-Strain Characteristics of Vulcanized or Thermoplastic Rubber", and the compression permanent deformation rate of 200°C×70h was tested according to "GB / T 7759-2015 Determination of Compression Permanent Deformation of Vulcanized Rubber or Thermoplastic Rubber at Normal Temperature, High Temperature and Low Temperature", and the test results are shown in Table 1 below:

[0126] Table 1

[0127]

[0128] As shown in Table 1, by comparing Preparation Examples 1-3 with Preparation Examples 4-5, it can be seen that during the preparation process, the vinyl content and viscosity of the hydroxyl-terminated polymethylvinylsiloxane and the specific surface area of ​​fumed silica will affect the mechanical properties of the foamed silicone rubber, such as tensile strength and compressive stress. Among them, the vinyl content and viscosity of the hydroxyl-terminated polymethylvinylsiloxane will affect its own dispersibility, crosslinking and foaming rate with the silicone rubber. As shown in Preparation Examples 3 and 5, the higher the vinyl content, the greater the foaming ratio of the silicone rubber, and the lower the density of the formed silicone rubber. The tensile strength will also be affected to a certain extent. As shown in Preparation Examples 2 and 4, when the vinyl content is too low, the crosslinking and foaming of the silicone rubber will be affected. Although the density of the foamed silicone rubber is increased, its crosslinking is low and the tensile strength will not be improved. Moreover, through the comparison of Preparation Examples 1, 4 and 5, it can be seen that when the modified carbon nanotubes are applied to the foamed silicone rubber, although the use of a large amount of modified carbon nanotubes can effectively improve the compression deformation resistance of the foamed silicone rubber, the use of carbon nanotubes will affect the tensile strength of the foamed silicone rubber.

[0129] Furthermore, by comparing Preparation Example 4 with Preparation Example 6, and by comparing Preparation Example 5 with Preparation Example 7, it can be seen that within the usage range of modified carbon nanotubes specified in the present application, the usage of modified carbon nanotubes directly determines the compressive deformation resistance of the molded foamed silicone rubber material. However, by comparing Preparation Example 1 with Preparation Example 5, it can be seen that when the usage of modified carbon nanotubes increases to a certain extent, the compressive deformation resistance of the molded foamed silicone rubber will not be infinitely improved. On the contrary, the tensile strength will be reduced due to the cross-linking of carbon nanotubes and silicone rubber.

[0130] In addition, through the comparison between Preparation Examples 1-7 and Comparative Preparation Examples 1-2, it can be seen that the modified carbon nanotubes have significantly improved the compression deformation resistance of the molded foamed silicone rubber, so that this type of foamed silicone rubber material can not only perform shock-absorbing treatment on the new energy battery through compression deformation when used in the support work of new energy batteries, but also effectively control the amount of compression deformation, and will not cause an increase in density like rubber materials, resulting in an increase in the cost of use.

[0131] By comparing Preparation Example 4 with Comparative Preparation Example 3 and Preparation Example 5 with Comparative Preparation Example 6, it can be seen that when the amount of modified carbon nanotubes used is too small, the compression deformation resistance of the foamed silicone rubber cannot be effectively improved, and when the amount of modified carbon nanotubes used is too much, as mentioned above, it will cause cross-linking problems, resulting in a decrease in tensile strength. Therefore, the amount of modified carbon nanotubes used needs to form a dynamic balance with the original mechanical reinforcement agent.

[0132] By comparing Preparation Examples 1-7 with Comparative Preparation Examples 5-6, it can be seen that when the carbon nanotubes are not modified by shear enhanced gel, the improvement of the compression deformation resistance of the foamed silicone rubber by the carbon nanotubes is negligible. When the surface of the carbon nanotubes is not treated to form vinyl functional groups, the compatibility problem between the carbon nanotubes and the silicone rubber will cause the tensile strength of the foamed silicone rubber to be greatly reduced, which cannot meet the use requirements.

[0133] In summary, if Figure 2-Figure 8 As shown, the foamed silicone rubber prepared in Preparation Examples 1-7 of the present invention has a rich pore structure, which gives the foamed silicone rubber excellent shock-absorbing ability. However, through the use of modified carbon nanotubes, the hardness and compression deformation resistance of the molded foamed silicone rubber are significantly improved, so that the foamed silicone rubber has shock-absorbing ability while having strong compressive deformation resistance.

[0134] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high hardness foamed silicone rubber, characterized in that: By weight, including: 1-20 parts of hydrogen-containing polysiloxane; 10-70 parts of hydroxyl-terminated polymethylvinylsiloxane; Mechanical reinforcing agent 1-30 parts; Flame retardant 10-80 parts; Catalyst 0.05-0.3 parts; Wherein, the vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.1%-6%, the viscosity is 500-50000mPas, and the hydroxyl content is 0.4%; The mechanical reinforcing agent comprises filler 1, filler 2 and filler 3 in a weight ratio of 3:6:1-3:3:1, wherein filler 1 is fumed silica surface-treated with methylvinylsilazane, and the specific surface area of ​​the fumed silica is 100-400m 2 / g, the filler 2 is a vinyl MQ silicone resin, the viscosity of the vinyl MQ silicone resin is 2000-100000 mPas, and the vinyl content is 1-8%, the filler 3 is a modified carbon nanotube, the carbon nanotube is a carbon nanotube with both ends opened, and a shear thickening gel is adsorbed inside the carbon nanotube, and the shear thickening gel is a lightweight shear thickening gel; The flame retardant is aluminum hydroxide surface-treated with vinyltriethoxysilane, and the particle size of the aluminum hydroxide is 1 micron; The catalyst is a Castell platinum catalyst, and the platinum concentration of the Castell platinum catalyst is 5000 ppm.

2. The high-hardness foamed silicone rubber according to claim 1, characterized in that: The carbon nanotubes are modified carbon nanotubes having vinyl groups on the surface.

3. The high-hardness foamed silicone rubber according to claim 1, characterized in that: The carbon nanotubes are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes. The diameter of the carbon nanotubes is 10-30 nm, and the length of the carbon nanotubes is 1-3 μm.

4. The high-hardness foamed silicone rubber according to claim 1, characterized in that: The vinyl content of the hydroxyl-terminated polymethylvinylsiloxane is 0.2-2%, and the viscosity of the hydroxyl-terminated polymethylvinylsiloxane is 4000-6000 mPa.s; the specific surface area of ​​the fumed silica is 250-350 m 2 / g.

5. A method for preparing the high-hardness foamed silicone rubber according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step a, by weight, adding 9-63 parts of hydroxyl-terminated polymethylvinylpolysiloxane, 10-80 parts of flame retardant, and 10-30 parts of mechanical reinforcing agent into a planetary mixer, stirring at room temperature for 1 hour to obtain a base material, and dividing the base material into two parts, namely component A and component B; Step b, adding 1-20 parts of hydrogen-containing polysiloxane to component A and stirring evenly to obtain material A; Step c, adding 1-7 parts of hydroxyl-terminated polymethylvinyl polysiloxane and 0.05-0.3 parts of Castaplatin catalyst to component B and stirring evenly to obtain material B; Step d: Take one portion of material A and one portion of material B in a weight ratio of 1:1, mix them quickly and evenly, and obtain foamed silicone rubber A after reacting for 10 minutes. Put the foamed silicone rubber A into a 200° C. oven and bake it for 1 hour to obtain foamed silicone rubber B.

6. The method for preparing a high-hardness foamed silicone rubber according to claim 5, characterized in that: The method for preparing the flame retardant in step a comprises the following steps: Add 100 parts of aluminum hydroxide into a high-speed mixer, start stirring and add 1 part of vinyl triethoxysilane into the mixer by spraying, stir at room temperature for 10 minutes, then increase the temperature in the mixer to 90°C and stir for 2 hours, then increase the temperature to 150°C and continue stirring for 30 minutes to obtain a flame retardant.

7. The method for preparing a high-hardness foamed silicone rubber according to claim 5, characterized in that: The preparation method of the filler 1 contained in the mechanical reinforcement agent in step a comprises the following steps: Add 5 parts of fumed silica to a high-speed mixer, start stirring and dropwise add 1 part of tetramethyldivinylsilazane to the mixer, stir at room temperature for 2 hours, then raise the temperature in the mixer to 90°C and stir for 2 hours, then raise the temperature to 150°C and continue stirring for 5 hours to obtain filler 1.

8. The method for preparing a high-hardness foamed silicone rubber according to claim 5, characterized in that: The preparation method of the filler three contained in the mechanical reinforcing agent in step a comprises the following steps: Step a1, soaking 10 parts of carbon nanotubes in a mixed acid composed of sulfuric acid and nitric acid, the mixed acid is prepared by mixing and reacting at 105-115° C., wherein the mass ratio of sulfuric acid to nitric acid is 2-4:1, so that the surface of the carbon nanotubes is carboxylated, and at the same time, the openings at both ends of the carbon nanotubes are opened by using a strong acid; Step a2, at 30-50° C., adding tetraethyl orthosilicate and vinyl triethoxysilane to a mixed solution of water and ethanol in which surface carboxylated carbon nanotubes are dissolved, and simultaneously adding part of ammonia water for reaction; then adding the remaining mixture and ammonia water respectively, wherein the feed mass ratio of the surface carboxylated carbon nanotubes, the mixture of tetraethyl orthosilicate and vinyl triethoxysilane, and ammonia water is 1:1.1:1.1, the feed mass ratio of water to ethanol is 1:1.05, and the feed mass ratio of one of tetraethyl orthosilicate and vinyl triethoxysilane to the other is controlled within 3 times, and after the reaction is completed, modified carbon nanotubes with open ends and vinyl groups on the surface are obtained; Step a3: After the prepared modified carbon nanotubes are rinsed with clean water and dried, the carbon nanotubes are mixed with a shear thickening gel and immersed for 3 hours. The carbon nanotubes are sieved out from the shear thickening gel and dried to obtain filler three.

9. The method for preparing a high-hardness foamed silicone rubber according to claim 5, characterized in that: In the step d, the obtained foamed silicone rubber B has a Shore A hardness of 30-60 and a density of 0.6-0.8 g / cm 3 , tensile strength is 0.8-1.5MPa, flame retardancy is V0, and compressive stress is 200-400kPa under 10% compressive strain.

Citation Information

Patent Citations

  • Silicone rubber foam material and its preparation method

    CN114621495B

  • Foaming conductive silicone rubber and preparation method thereof

    CN116285365A

  • Formed-in-place foamed silicone rubber sealing ring composition and preparation method thereof

    CN110256853A

  • Preparation method and application of modified carbon nanotube

    CN110921654A

  • Silicone rubber foam material and preparation method thereof

    CN114621495A